Analisis Pengembangan Profesionalisme Guru Berkelanjutan Di SMK Negeri 2 Sragen - Suprianto, Sapto Edy (2016)
The purpose of this study was to describe (1) Characteristics of ongoing teacher professional development for teachers certified in SMK Negeri 2 Sragen. (2) the characteristics of the difficulties faced by teachers certified in the continuous professional development of teachers at SMK Negeri 2 Sragen. (3) Efforts to overcome the problems of teachers in the development of sustainable profesionalism in SMK Negeri 2 Sragen. The research is a qualitative study with ethnographic research design. Location of the research conducted at SMK Negeri 2 Sragen. The study used ethnographic design (Ethnographic Research). Data collection techniques using in-depth interviews, documentation, and observation. Analysis of the data by using three stages: data reduction, data presentation, and drawing conclusions with verification. Results of this study were (1) professional development activities in the form of KTI, created by the teacher basically still is seasonal, meaning not yet done periodically. Scientific papers (KTI) development activities in particular make classroom action research (PTK) oriented form of mastery learning material which is focused on the needs of students who deepening of the material, carried out in collaboration with colleagues. (2) The difficulties faced by teachers certified include the interest to carry out the development and writing skills of teachers, time constraints, factors qualifications and educational background is not appropriate, the necessary competence not support, the income is not in accordance with work performance, lack of opportunities for professional development on an ongoing basis , no attempt by the authorities to encourage teachers, teachers are less motivated, usage habits monotonous teaching methods and skills of teachers in implementing the floating profession is still low. External issues include: the teacher does not have the background knowledge and skills strongly about the development of the profession, the working environment of teachers who are less supportive, Indonesian Teachers Association (PGRI) has not played an active role. (3) The efforts made by teachers, government and schools are: Planting of understanding of the professional standards of teachers by principals to teachers through coaching routine, establish a good working relationship and extensive including through professional organizations, including through professional organizations, develop a work ethic or work culture that prioritizes service high quality to the public, through coaching, teachers are given the opportunity to attend seminars, technical guidance and workshops professional development, teacher familiarized with the use of information technology both as a means of carrying out administrative tasks and tasks of teaching, teachers are given the opportunity to do a comparative study with the school kind of more advanced, teachers are given the opportunity to participate in advanced courses, as well as the adjustment to college education, and improving the competence of teachers through coaching and training